Between Surface and Summit: the Process of Mound Construction at Feltus. Issue 1 (4th February 2014) - Kassabaum, Megan C.; Henry, Edward R.; Steponaitis, Vincas P.; O'hear, John W.; Thompson, Victor D.
ABSTRACT Geophysical methods that explore depths more than 1 m below the surface were employed at Feltus (22Je500), a Coles Creek period (ad 700–1200) mound‐and‐plaza group in southwestern Mississippi, USA. It is difficult to assess the internal structure of large platform mounds such as those at Feltus using excavation and traditional geophysical techniques alone. As a result, such investigations often focus only on activities that took place during and after the final stage(s) of construction. Our 2012 research at Feltus utilized electrical resistivity tomography and downhole magnetic susceptibility to examine the internal structure of two platform mounds at depths beyond those commonly targeted by shallow techniques. These methods revealed mound stages, prepared floors, midden and pit features, and construction attributes within the fill episodes. By refocusing our attention on the process of mound building rather than the final use of the mound summits, this research broadened our view of the role of monuments in creating and strengthening community ties. Copyright © 2014 John Wiley & Sons, Ltd.